Introduction and Table of Contents - Mary Rodriguez (Journal of International Agricultural and Extension Education, 2022)
The Journal of International Agricultural and Extension Education is the official refereed publication of the Association for International Agricultural and Extension Education (AIAEE). Its purpose is to enhance the research and knowledge base of agricultural and extension education from an international perspective.